Prototype Pintu Air Irigasi Otomatis Berbasis Internet Of Things - Erwan Darmawan; Iqbal Fernando; Edna Maryani; Ghina Rizqandi Qurrota A'yun (Jurnal Ilmiah Sains dan Teknologi, 2025)
Abstract A sluice gate is a supporting structure in a dam, reservoir, river, gutter or ditch which functions to regulate the control of water discharge in each flow. With good and controlled irrigation, irrigation systems and waterways from upstream to downstream can be controlled, so that the need for water in agriculture, fisheries, plantations, and industry can be met and relied on properly. The sluice gate functions to control water so that it can prevent flood water in a fast and high flow. The flowing water will lead to the river to the ocean. Therefore the author will design a prototype of an Internet of Things (IoT) based automatic sluice monitoring system. this system requires interrelated components, namely NodeMcu as the control center of the system as well as a wifi module and the relay module as an electrical switch to turn on or off and use the blynk application.